DOT1L-controlled cell-fate determination and transcription elongation are independent of H3K79 methylation - Cao, Kaixiang (Proc Natl Acad Sci U S A, 2020)
Actively transcribed genes in mammals are decorated by H3K79 methylation, which is correlated with transcription levels and is catalyzed by the histone methyltransferase DOT1L. DOT1L is required for mammalian development, and the inhibition of its catalytic activity has been extensively studied for cancer therapy; however, the mechanisms underlying DOT1L’s functions in normal development and cancer pathogenesis remain elusive. To dissect the relationship between H3K79 methylation, cellular differentiation, and transcription regulation, we systematically examined the role of DOT1L and its catalytic activity in embryonic stem cells (ESCs). DOT1L is dispensable for ESC self-renewal but is required for establishing the proper expression signature of neural progenitor cells, while catalytic inactivation of DOT1L has a lesser effect. Furthermore, DOT1L loss, rather than its catalytic inactivation, causes defects in glial cell specification. Although DOT1L loss by itself has no major defect in transcription elongation, transcription elongation defects seen with the super elongation complex inhibitor KL-2 are exacerbated in DOT1L knockout cells, but not in catalytically dead DOT1L cells, revealing a role of DOT1L in promoting productive transcription elongation that is independent of H3K79 methylation. Taken together, our study reveals a catalytic-independent role of DOT1L in modulating cell-fate determination and in transcriptional elongation control.